Further Turkish Loanwords in the Cretan Dialect of Modern Greek - Kaczyńska, Elwira; Witczak, Krzysztof Tomasz (Folia Orientalia, 2026)
Five years ago Vasilis Orfanos published an excellent monograph on the Turkish lexical borrowings attested in the Cretan dialect of Modern Greek (Orfanos 2014). In this paper the present authors increase the number of the possible Cretan Turkisms, providing and explaining additional items not listed in Orfanos’s book.